Transparency as trade policy: Value of advance notifications in technical regulations - Irene Iodice (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Lack of advance information about regulatory changes in destination markets increases uncertainty over compliance costs. This paper quantifies the value of advance notification using newly compiled WTO Technical Barriers to Trade (TBT) timelines matched to detailed French firm-product-destination export data for 1995-2007. When regulations are notified before enforcement, the export-participation loss from TBTs falls by more than half (from 7 to 3 percentage points), driven by fewer temporary exits and greater entry among smaller firms. Exploiting cases of delayed notification, I show that exports rebound immediately once information becomes available, indicating that uncertainty-rather than adjustment time-is the key mechanism. A heterogeneous-firm real-options model explains this pattern: by narrowing the dispersion of possible regulatory outcomes, advance notice reduces the option value of waiting. Calibrated tariff equivalents imply that timely notification can be worth up to 28 percentage points.
Keywords: F13; F14; D84; 330